'It's okay to be racist': moral disengagement in online discussions of racist incidents in Australia. Issue 14 (13th November 2016) - Faulkner, Nicholas; Bliuc, Ana-Maria
ABSTRACT: Racist views expressed on the Internet have damaging consequences for social harmony and well-being. This article examines how and why individuals express support or opposition to racist behaviour in a prominent online medium: comments on news websites. Specifically, we examine how supporters and opponents of racist behaviour use a particular type of subtle discursive strategies known as moral disengagement in their online responses to three notable racist incidents that occurred in Australia in 2013. Moral disengagement strategies allow individuals to avoid distress, self-condemnation, and social-sanctions when supporting or engaging in harmful behaviour by making that behaviour appear moral and acceptable. We show that supporters, but not opponents, of racist behaviour consistently use moral disengagement strategies in their rhetoric, and demonstrate that moral disengagement provides a powerful theoretical framework through which racist rhetoric on online news websites can be understood.